The Indonesian Government's Efforts to Protect Indonesian Migrant Workers Threatened with the Death Penalty Abroad - Surya Perdana (RIRAI Publisher, 2023)
This study will look at the protection provided by the law for Indonesian workers who are threatened with the death sentence overseas and the steps taken by the administration to provide such protection. migrant workers from Indonesia or Indonesian Migrant Workers are parties who are very vulnerable to indecent treatment, physical and psychological violence, intimidation, discrimination, and injustice. Collecting data in research using normative study. Sexual violence experienced by female migrant workers or PMI is often the beginning of cases of murder committed by these workers in self-defence. In the end, cases like this in local courts sentence TKI or PMI with the death penalty. This study concludes that the concept of legal protection carried out by the government in recent years can reduce the number of TKI or PMI who are subject to capital punishment because the victims' families forgive them.